Study of regulations on Technology matter of obligatory secondary education: the case of Asturias - Luis Ángel Tamargo Pedregal; Susana Agudo Prado; Javier Fombona Cadavieco (Centro de Estudios Financieros, 2016)
This article describes, in the specific context of the Autonomous Community of Asturias (Spain) the legislative journey of the curricula of the subject Technology of obligatory secondary education (OSE), since its introduction in the early nineties of the twentieth century until today, after the approval of the organic Law 8/2013 for the improvement of educational quality (LOMCE), and the evolution of its workload until now. Also, we analyze, through the development of comparative tables, various curricula issued to over the 25 year life of the subject in the region, with special attention to their thematic content and evaluation criteria described in each, to understand the major changes in this area.